Ministry Of Finance Decree No. 184 Of The Year 2017 Concerning The Rules Governing The Disbursement Of The Exceptional Cost Of Living Allowance Prescribed As Per Law No. 79 Of The Year 2017 to those Who Are Addressed By The Law On Civil Service Promulgated by Law No. 81 of the year 2016 And the Rules Governing the Disbursement of the Periodic Raise Prescribed Therefor = وزارة المالية قرار رقم 184 لسنة 2017 بشأن قواعد صرف علاوة الغلاء الاستثنائية المقررة بالقانون رقم 79 لسنة 2017 للمخاطبين بأحكام قانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016 وقواعد صرف العلاوة الدورية المقررة لهم - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic